The law and politics of transnational rights protection: Trusteeship, effectiveness, de‐delegation. Issue 1 (28th September 2022) - Stone Sweet, Alec; Sandholtz, Wayne
Abstract: International trustee courts embody a specific form of delegation, in which state principals confer on such courts the authority to interpret and apply treaties agreed by the states in order to realize specific values and interests. Human rights courts help states resolve commitment and enforcement problems that are inherent in human rights treaties. This study seeks to answer the question, what happens when states parties seek to reduce or eliminate the authority of a human rights court? To answer these questions, the article assesses six human rights treaty regimes: the Council of Europe; the Organization of American States; the African Union; the Economic Community of West African States; the East African Community; and the Southern African Development Community. The article identifies four types of de‐delegation possible with respect to international human rights courts and assesses the extent to which states have sought to de‐delegate from them. With one exception (the SADC Tribunal), the regimes examined here have so far successfully withstood the challenge of de‐delegation.